THE RELATION BETWEEN THE MUSCULAR STRENGTH OF PATIENTS WITH OSTEOARTHRITIS AND THE DEGREE OF JOINT DETERIORATION (Fiep Bulletin - online, 2014)
Patients with osteoarthritis of the knee present muscular weakness especially in extensors and flexors, in other words, muscles that are considered primary motors of many functional activities. Objectives: In this work was valued the concentric and eccentric torque of flexors and extensors of the knee of patients with osteoarthritis of the knee and related with the degree of the joint deterioration. Methodology: The sample was constituted of 12 subjects, 7 women and 5 men, with average age of 61,08 ±3,82 years old. The maximum torque was obtained through the isokinetic dynamometer (Kin-Com) in the angular speed of 60 °/s, the degree of the joint deterioration was obtained through the analysis of the radiographic examination by a radiologist who followed the radiological graduation of Kellgren-Lawrence. Results: Comparing, separately, the degrees of the joint deterioration 2 and 4 or 3 and 4 in the inferior right member and the degrees 1 and 2 in the left one, we could notice that with the raise of the joint deterioration in patients with osteoarthritis takes place a reduction on the average of the maximum torque, however this relation does not demonstrate statistically significant difference. In the relation between the maximum torque and the degree of the joint deterioration unilateral, the obtained values of TQC, TQE and TIE are bigger in the stricken member. Conclusions: The results of this research show reduction of strength in patients with osteoarthritis, however they cannot be considered conclusive for it being a small sample and with a high variability, further investigations are needed.
Keywords: Osteoarthritis; Knee; Torque; Biomechanics